FINANCIAL INCLUSION: WHAT AND HOW? EVIDENCE FROM AZERBAIJANI ECONOMY - Afgan Imanzade; Anar Zeynalov; Seymur Hasanov (Premier Publishing, 2017)
The main goal of the research is to study what financial inclusion is and analyse its current status in the Azerbaijani economy. To that end, the monography analyses infrastructural elements to be shaped to make financial resources and services available, and the potential to deepen financial inclusion, researches international practice with respect to elements of financial infrastructure affecting stronger financial inclusion and includes case studies. The study also analyses the status of financial inclusion in the Republic of Azerbaijan as part of measuring financial inclusion and issues proposals on the actions to be taken.
Additional information: The paper is being planned to be published in September, 2017.
Keywords: K20; G21; G30; 330; access to finance; financial inclusion